2019
DOI: 10.5603/gp.2019.0039
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adverse perinatal outcomes in intrahepatic cholestasis of pregnancy

Abstract: Objectives:Our objective was to evaluate in our clinic the perinatal outcomes of patients diagnosed with ICP based on pre-treatment maternal serum bile acid levels, attempt to identify the risk group and review the literature in light of this information. Material and methods:In total, 370 patients diagnosed with ICP were included in the study, divided into two groups based on the fasting total serum bile acid level before UDCA (Group 1: 10 ≥ 40 μmol/L, and Group 2: ≥ 40 μmol/L). The groups were examined for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Mean age of women was 25.25 ± 3.61 years in the study group. In a similar study, Renu et al [6] and Celik et al [13] described that mean age of 26.42 ± 5.79 years and 27.7 ± 5.3 years was found in their study subjects. Their findings were consistent with the finding found in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…Mean age of women was 25.25 ± 3.61 years in the study group. In a similar study, Renu et al [6] and Celik et al [13] described that mean age of 26.42 ± 5.79 years and 27.7 ± 5.3 years was found in their study subjects. Their findings were consistent with the finding found in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…Although many studies have shown that a high level of serum bile acid causes adverse perinatal outcomes in singleton pregnancies [5][6][7][8][9][10][11], few studies exist on cholestasis in multiple pregnancies. This study aimed to compare the perinatal outcomes of normal twin pregnancies and twin pregnancies involving ICP in a group of 700 participants.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the use of biophysical profile and Doppler, babies may die [15]. Premature rates in obstetric cholestasis vary from 19% to 66% [16,17]. In our study, this rate was determined to be 34%.…”
Section: Discussionmentioning
confidence: 60%